2022
DOI: 10.1186/s12890-022-01910-6
|View full text |Cite
|
Sign up to set email alerts
|

Paradoxical development of pleural-based masses in patients with pleural tuberculosis during treatment: a clinical observational study in China

Abstract: Background To explored the clinical, pathological, and bacteriological characteristics of pleural-based masses occurred during anti-tuberculosis (TB) treatment in patients with pleural TB. Methods Patients referred with newly diagnosed pleural TB were prospectively enrolled into the study. Patients were followed up throughout the treatment, and clinical data were recorded. Percutaneous biopsy and surgical tissues from pleural-based masses were exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Besides, the average onset time of PTM in this study was found to be 4.67 ± 2.41 months after the TPE diagnosis. This nding aligns with previous studies that have shown the onset of PTM typically occurs within 6 months after diagnosis [10].…”
Section: Discussionsupporting
confidence: 92%
“…Besides, the average onset time of PTM in this study was found to be 4.67 ± 2.41 months after the TPE diagnosis. This nding aligns with previous studies that have shown the onset of PTM typically occurs within 6 months after diagnosis [10].…”
Section: Discussionsupporting
confidence: 92%